Answer:
1) 34 + 0i
2) 9/17 + (2/12)i
3) z = -i
Explanation:
Part 1:
(5 + 3i)(5 - 3i) = 25 - 15i + 15i - 9i²
25 - 15i + 15i - 9i² = 25 - 9i²
25 - 9i² = 25 - 9√(-1)²
25 - 9√(-1)² = 25 - 9(-1)
25 - 9(-1) = 25 + 9
25 + 9 = 34
34 = 34 + 0i
Part 2:
(2 + i) / (4 + i)
![(a+bi)/(c+di)\:=\:(\left(c-di\right)\left(a+bi\right))/(\left(c-di\right)\left(c+di\right))\:=\:(\left(ac+bd\right)+\left(bc-ad\right)i)/(c^2+d^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p3wmfyfqdtpayjhym5unh3loexgoi93kkq.png)
a=2, b= 1 , c=4 , d =1
![(\left(2\cdot \:4+1\cdot \:1\right)+\left(1\cdot \:4-2\cdot \:1\right)i)/(4^2+1^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yd696qbfndxympc5nn0b22mnsmf30vm6om.png)
![(9)/(17)+(2)/(17)i](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6uw97zkkrj15x3qzqxjk8gbf5n00o8w30n.png)
Part 3:
![(z+1)/(z-1)=i\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b89lgp5k83xnz3dxlbyzseo70ejx2bz06c.png)
Solve like part 2:
z = -i